2009
DOI: 10.1029/2009wr007944
|View full text |Cite
|
Sign up to set email alerts
|

An objective analysis of the dynamic nature of field capacity

Abstract: Field capacity is one of the most commonly used, and yet poorly defined, soil hydraulic properties. Traditionally, field capacity has been defined as the amount of soil moisture after excess water has drained away and the rate of downward movement has materially decreased. Unfortunately, this qualitative definition does not lend itself to an unambiguous quantitative approach for estimation. Because of the vagueness in defining what constitutes “drainage of excess water” from a soil, the estimation of field cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 27 publications
5
135
0
Order By: Relevance
“…Therefore, Romano and Santini (2002) argued that a field drainage experiment is the test to be preferred for determining the water content value at field capacity, namely the condition when drainage fluxes become virtually nil during a redistribution process started from an initially saturated soil profile and with no flux from the soil surface. Using the HYDRUS-1D software to simulate field drainage experiments for real soils retrieved from different soil databases, Twarakavi et al (2009) confirmed the inaccuracy of determining field capacity from pre-fixed points of the water retention curve. They also suggested that the value of 0.01 cm day −1 can be considered as a negligible drainage flux being imposed at the lower limit of the rooting zone to meet the condition of field capacity for a wide range of soils.…”
Section: Techniques For Determining Field Capacitymentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, Romano and Santini (2002) argued that a field drainage experiment is the test to be preferred for determining the water content value at field capacity, namely the condition when drainage fluxes become virtually nil during a redistribution process started from an initially saturated soil profile and with no flux from the soil surface. Using the HYDRUS-1D software to simulate field drainage experiments for real soils retrieved from different soil databases, Twarakavi et al (2009) confirmed the inaccuracy of determining field capacity from pre-fixed points of the water retention curve. They also suggested that the value of 0.01 cm day −1 can be considered as a negligible drainage flux being imposed at the lower limit of the rooting zone to meet the condition of field capacity for a wide range of soils.…”
Section: Techniques For Determining Field Capacitymentioning
confidence: 95%
“…The actual transpiration rate is then calculated on the basis of the actual soil water extraction rate over the whole rooting depth. Further details on this module of the model can be found in Kroes and van Dam (2003) and van Dam et al (2008). Of specific interest for this study is the semi-empirical way with which the uptake reduction function, α(h), is modeled by SWAP (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this classical static approach based on benchmark pressure-can be criticized, field capacity being attached to water retention values rather than hydraulic conductivity characteristics of soils. The evaluation of SWHC using field capacity values defined as the soil water content when the drainage flux become negligeable could be a solution to overcome these limits (Twarakavi et al, 2009). Improvements could also be made by using the integral energy principle, a method based on the entire soil water retention curve to evaluate the energy required by plants to remove soil water, avoiding to consider water between the two potentials is equally available (Minasny and McBratney, 2003).…”
Section: Uncertainties Linked To the Soil Water Estimationmentioning
confidence: 99%
“…Based on this dependence and on the operational difficulties of the field test, FC is also commonly evaluated in a laboratory setting as the water content of undisturbed soil samples (or disturbed samples, which is less acceptable) at a specific soil water matric potential. Cassel & Nielsen (1986), Romano & Santini (2002) and Nemes et al (2011) reported that a wide range of matric potentials (from -2.5 to -50 kPa) have been used for this purpose, although suctions of 5, 6, 10, and 33 kPa are more common choices; however, there is no satisfactory general criterion for the selection of the suction values for this kind of FC determination (Hillel, 1998;Twarakavi et al, 2009;Nemes et al, 2011). Taking into account the dynamic nature of drainage in field FC evaluations, some authors (Nachabe et al, 2003) argue that the definition of FC must be based on a particular choice for the "negligible" downward flux, instead of the usual drainage time of two or three days, or the suction at FC.…”
Section: Introductionmentioning
confidence: 99%